Design, synthesis, and spectroscopic study of 7-azaindolyl hydrazones with anti-breast cancer activity - Dongare, Sakharam B. (Array, 2019)
A series of 7-azaindolyl hydrazones were prepared by reacting of hydrazides of 7-azaindole-3-acetic acids with aromatic aldehydes and N-substituted indolyl-3-carboxyaldehydes. Structure of all the synthesized compounds were satisfactorily correlated by IR, 1H NMR, 13C NMR and mass spectroscopic evidences. The synthesized compounds were evaluated for their possible anticancer potential against MCF-7 induced breast carcinoma. It is worth mentioning that most of the compounds were considerably active against MCF-7 cell line with GI50 values ranging from 22.3–81.0 μM. The hydrazones of N-1-substituted indole-3-carboxyaldehydes 9f, 9g, 9h, 9c, and 9j were active against MCF-7 cell line with GI50 values less than 40 μM (GI50 = 22.3 and 24.9, 29.6, 30.2 and 37.8 μM respectively) with moderate TGI values (TGI = 56.6, 59.5, 65.5, 70.7 and 94.6 μM respectively). The active compounds were also screened against the normal Vero monkey cell line, which showed moderate selectivity against inhibition of cancer cells.